Evaluation of the effect of precursor ratios on the electrochemical performances of binder-free NiMn-phosphate electrodes for supercapattery - Gerard O.; Ramesh S.; Ramesh K.; Numan A.; Norhaffis Mustafa M.; Khalid M.; Tiong S.K. (Academic Press Inc., 2025)
Binary metal phosphate electrodes have been widely studied for energy storage applications due to the synergistic effects of two different transition elements that able to provide better conductivity and stability. Herein, the battery-type binder-free nickel-manganese phosphate (NiMn-phosphate) electrodes were fabricated with different Ni:Mn precursor ratios via microwave-assisted hydrothermal technique for 5 min at 90 C. Overall, NiMn3P electrode (Ni:Mn = 1:3) showed an outstanding electrochemical performance, displaying the highest specific (areal) capacity at 3 A/g of 1262.4 C/g (0.44 C/cm2), and the smallest charge transfer resistance of 108.8 . The enhanced performance of NiMn3P electrode can be ascribed to the fully grown amorphous nature and small-sized flake and flower structures of NiMn3P electrode material on the nickel foam (NF) surface. This configuration offered a higher number of active sites and a larger exposed area, facilitating efficient electrochemical reactions with the electrolyte. Consequently, the NiMn3P//AC electrode combination was chosen to further investigate its performance in supercapattery. The NiMn3P//AC supercapattery exhibited remarkable energy density of 105.4 Wh/kg and excellent cyclic stability with 84.7% retention after 3000 cycles. These findings underscored the superior electrochemical performance of the battery-type binder-free NiMn3P electrode, and highlight its potential for enhancing the overall performance of supercapattery. ? 2024 Elsevier Inc.